The evaluation of the research on the arts and humanities in Turkey: A scientometric approach - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of the research on the Arts & Humanities carried out by the researchers in Turkey and published during the last three decades based on the Arts & Humanities Citation Index (A&HCI) and its implications using the scientometric techniques. The results of this study reveal that the research output on the Arts and Humanities and the citations received have grown exponentially during this period especially during the 2000s with paralleling enormous changes in the research landscape. However, the research performance of the researchers in Turkey in the fields of Arts and Humanities (1,705 papers and 1,745 citations) have lagged significantly behind the comparitive performance of Turkey in the Social Sciences but especially in Hard Sciences like Engineering and Health Sciences. The US, England, and France have been the three most prolific collaborating countries. The "Bilkent Univ" has been the most prolific instituion and "Almond I" of "Bilkent Univ" has been the most prolific author. "Milli Folkor" (National Folklore) has been the most prolific journal whilst "Archaeology" has been the most prolific subject area. "H-index" was 16 and "Kita & Ozyurek" [1] has had the highest impact on the literature. The scientometric analysis has a great potentail to gain valualbe insights into the evolution of the research on the Arts and Humanities in Turkey, complementing the scientometric studies in the other fields such as renewable energies as well as students with disabilities providing a unique insight on the incentive structures for all the key stakeholders in the field. It was concluded in this context that the incentive structures have not been well designed to produce superior research performance in Arts & Humanities in Turkey as in Hard Sciences such as Engineering and Health Sciences especially in the design of the rules for the academic appointments and promotions in universities.
Keywords: Web of Knowledge; Arts; Humanities; Architecture; A&HCI; Incentive structures; Research evaluation; Research productivity; Scientometrics